Designing A Social Media Style Guide For PT. Xxx Brand Identity - Prasetyo, Andreas Recki; Revinzky, Muhammad Aqshel (CV Putra Publisher, 2024)
Rapid technological advances have encouraged companies to explore new platforms and strategies to increase public visibility and recognition. In the context of increasingly fierce competition, companies need to develop effective strategies and build a strong brand identity in order to stand out and survive in this industry. Social media has become a very important tool in efforts to build brand identity. Therefore, the development of a comprehensive social media style guide is essential. This study uses a descriptive qualitative approach in the form of a project study with the aim of formulating a social media style guide that can provide clear direction and policies. This guide aims to encourage consistency and strengthen the company's brand identity on social media platforms. The research process begins with an analysis of internal and external factors that influence social media strategy, followed by the development of a style guide. The results of the study indicate that a structured and directed social media style guide can improve content consistency and contribute significantly to strengthening brand identity on social media.